Letter from Campbell Morfit to James Curtis Booth, April 21, 1860 - Morfit, Campbell (1860)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes with repayment of a $10 loan.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897